2017
DOI: 10.1002/tcr.201700022
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Application of Graphene Supported Metal Nanoparticles in C−C and C−X Coupling Reactions

Abstract: The carbon-carbon and carbon-heteroatom bonds catalytic formation is among the most significant reactions in organic synthesis which extensively applied for synthesis of natural products, heterocycles, dendrimers, biologically active molecules and useful compounds. This review provides the latest advances in the preparation of graphene supported metal nanoparticles and their application in the catalytic formation of both carbon-carbon (C-C) and carbon-heteroatom (C-X) bonds including the Suzuki, Heck, Hiyama, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(42 citation statements)
references
References 208 publications
(128 reference statements)
0
42
0
Order By: Relevance
“…Composites based on graphene, as a novel nanomaterial, have attracted extensive attention in the field of catalysis due to their unique characteristics, such as a large surface area, chemical stability, strong hydrophobicity and easy modification . Recent calculations and experiments have shown that graphene‐supported palladium has excellent catalytic activity for carbon–carbon cross‐coupling reactions because graphene has a high binding energy with palladium and good charge storage performance .…”
Section: Graphenementioning
confidence: 99%
“…Composites based on graphene, as a novel nanomaterial, have attracted extensive attention in the field of catalysis due to their unique characteristics, such as a large surface area, chemical stability, strong hydrophobicity and easy modification . Recent calculations and experiments have shown that graphene‐supported palladium has excellent catalytic activity for carbon–carbon cross‐coupling reactions because graphene has a high binding energy with palladium and good charge storage performance .…”
Section: Graphenementioning
confidence: 99%
“…The Sonogashira coupling between terminal alkynes and aromatic halides has been studied using different palladium species, mainly PdNPs, immobilized on carbonaceous materials such as carbon nanotubes, graphene-derived materials [51] and carbon itself. In general, good activity and recyclability have been observed when employing supported PdNPs, especially when activated electrophiles, such as aryl iodides and bromides are coupled with aromatic terminal alkynes.…”
Section: Carbon-based Material-supported Palladium Catalystsmentioning
confidence: 99%
“…In addition, practical limitations, such as catalyst operation, reusability, and isolation of the catalyst from products, hinder the advantages of homogeneous Pd catalysts in large-scale industrial processes. By contrast, a heterogeneous Pd catalyst could obviate these limitations and open up a valuable alternative technology in such processes [13][14][15][16][17]. In recent years, palladium nanoparticles (NPs) supported by various substrates, such as active carbon materials [18,19], silica [20][21][22], polymers [23,24], inorganic mineral [25,26], metal oxides [27][28][29], and covalent organic frameworks (COFs) [30,31] have been designed and applied for the Suzuki-Miyaura reaction.…”
Section: Introductionmentioning
confidence: 99%